A dual exchange rate system as an instrument of fiscal policy - Castañeda, Gonzalo (Estudios Económicos de El Colegio de México, 1992)
This paper studies the consequences of using a dual exchange rate regime as an instrument of fiscal policy. The emphasis is put on economies that depend heavily on oil revenues, such as the Mexican economy.